ATHENA X-IFU 300 K-50 mK cryochain demonstrator cryostat. (January 2018) - Prouvé, T.; Duval, J.M.; Charles, I.; Yamasaki, N.Y.; Mitsuda, K.; Nakagawa, T.; Shinozaki, K.; Tokoku, C.; Yamamoto, R; Minami, Y.; Le Du, M.; Andre, J.; et al.
Highlight: For ATHENA-XIFU, the demonstration of the 300 K–50 mK cooling chain is done in a GSE cryostat. Abstract: In the framework of the ESA X-ray mission ATHENA, scheduled for launch in 2028, an ESA Core Technology Program (CTP) was started in 2016 to build a flight like cryostat demonstrator in parallel with the phase A studies of the ATHENA/X-IFU instrument[1, 2] . As part of this CTP, called the Detector Cooling System (DCS), design, manufacturing and test of a cryostat including existing space coolers will be done. In addition to the validation of thermal performance, a Focal Plan Assembly (FPA) demonstrator using Transition Edge Sensors (TES) detector technology will be also integrated and its performance characterized versus the environment provided by the cryostat. This is a unique opportunity to validate many crucial issues of the cryogenic part of such a sensitive instrument. A dedicated activity within this CTP-DCS is the demonstration of the 300 K–50 mK cooling chain in a Ground System Equipment (GSE) cryostat. The studies are focused on the operation of the space coolers, which is made possible by the use of a ground cooler for cooling cryogenic shields and mechanical supports. Thanks to the modularity of the cryostat, several cooling chains could be tested. In the base line configuration described here, the low temperature stage is the CEA hybrid sorption/ADR 50 mK cooler with thermal interfaces at 4 K and 2 K. 4 K cooling is accomplished by a 4 K Joule-Thomson (JT) cryocooler and its Stirling precooler provided by JAXA. Regarding the 2 K stage, at first a 2 K JT from JAXA will be used. Alternatively, a 2 K JT cooler from RAL could replace the JAXA 2 K JT. In both cases new prototype(s) of a 2 K JT will be implemented, precooled by the EM 15 K pule tube cooler from Air Liquide. This test program is also the opportunity to validate the operation of the cryochain with respect to various requirements, such as time constant and temperature stabilities. This would bring us valuable inputs to integrate the cryochain in DCS cryostat or for the X-IFU phase A studies. This cryochain demonstration is also a critical milestone for the SPICA mission[3] . The design of the cryostat and first thermal validations both before and after integration of the JAXA JT coolers are presented in this paper.